Efficacy of apatinib 250 mg combined with chemotherapy in patients with pretreated advanced breast cancer in a real-world setting - Zhang, Ruyan; Chen, Yifei; Liu, Xiaoran; Gui, Xinyu; Zhu, Anjie; Jiang, Hanfang; Shao, Bin; Liang, Xu; Yan, Ying; Zhang, Jiayang; Song, Guohong; Li, Huiping (Frontiers in Oncology, 2023)
Objectives: This study evaluated the efficacy and safety of apatinib (an oral small-molecule tyrosine kinase inhibitor targeting VEGFR-2) 250 mg combined with chemotherapy in patients with pretreated metastatic breast cancer in a real-world setting. Patients and methods: A database of patients with advanced breast cancer who received apatinib between December 2016 and December 2019 in our institution was reviewed, and patients who received apatinib combined with chemotherapy were included. Progression-free survival (PFS), overall survival (OS), the objective response rate (ORR), the disease control rate (DCR), and treatment-related toxicity were analyzed. Results: In total, 52 evaluated patients with metastatic breast cancer previously exposed to anthracyclines or taxanes who received apatinib 250 mg combined with chemotherapy were enrolled in this study. Median PFS and OS were 4.8 (95% confidence interval [CI] = 3.2–6.4) and 15.4 months (95% CI = 9.2–21.6), respectively. The ORR and DCR were 25% and 86.5%, respectively. Median PFS for the previous line of treatment was 2.1 months (95% CI = 0.65–3.6), which was significantly shorter than that for the apatinib–chemotherapy combination (p < 0.001). No significant difference was identified in the ORR and PFS among the subgroups(subtypes, target lesion, combined regimens and treatment lines). The common toxicities related to apatinib were hypertension, hand-foot syndrome, proteinuria, and fatigue events. Conclusion: Apatinib 250 mg combined with chemotherapy provided favorable efficacy in patients with pretreated metastatic breast cancer regardless of molecular types and treatment lines. The toxicities of the regimen were well tolerated and manageable. This regimen could be a potential treatment option in patients with refractory pretreated metastatic breast cancers.